2015
DOI: 10.1016/j.molcel.2014.12.019
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Timeline of a Reviving Bacterial Spore

Abstract: SummaryThe bacterial spore can rapidly convert from a dormant to a fully active cell. Here we study this remarkable cellular transition in Bacillus subtilis and reveal the identity of the newly synthesized proteins throughout spore revival. Our analysis uncovers a highly ordered developmental program that correlates with the spore morphological changes and reveals the spatial and temporal molecular events fundamental to reconstruct a cell. As opposed to current knowledge, we found that translation takes place … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
173
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(192 citation statements)
references
References 44 publications
15
173
3
1
Order By: Relevance
“…We previously reported that the doubling time of the ⌬hpf mutant does not significantly differ from that of the WT (43 and 40 min, respectively) (21), and time-lapse microscopy studies failed to provide evidence that the ⌬hpf mutant continues to divide during stationary phase (data not shown). Previous work has demonstrated that bacteria can remain metabolically active without dividing (42,61,62). Taken together, these data suggest that hibernating ribosomes do not influence cell division but probably do have effects on other cellular activities.…”
Section: Discussionsupporting
confidence: 61%
“…We previously reported that the doubling time of the ⌬hpf mutant does not significantly differ from that of the WT (43 and 40 min, respectively) (21), and time-lapse microscopy studies failed to provide evidence that the ⌬hpf mutant continues to divide during stationary phase (data not shown). Previous work has demonstrated that bacteria can remain metabolically active without dividing (42,61,62). Taken together, these data suggest that hibernating ribosomes do not influence cell division but probably do have effects on other cellular activities.…”
Section: Discussionsupporting
confidence: 61%
“…While wild-type spores treated for ϳ20 h at 75 to 80°C retained almost normal viability even though almost all of their rRNA was lost, obviously rRNA must be synthesized in order for spores to grow out, since there is much protein synthesis in this period of spore development (13,(31)(32)(33)(34). To compare these wildtype spores' outgrowth kinetics, spores left untreated and spores treated at 75 or 80°C were incubated in medium that promoted spore germination, outgrowth, and subsequent vegetative growth and these processes were monitored by measuring the OD 600 of the incubated spores (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In spite of the evidence noted above, most of which is from work published 30 to 40 years ago, there are recent reports suggesting that metabolic activity does take place in dormant spores, including RNA synthesis and degradation, and that some protein synthesis takes place in and is required for the process of spore germination (12,13). Equally importantly, one of these reports suggested that these events in dormant spores could modify their germination properties significantly, in particular when spores were incubated for extended times at 37 to 50°C, leading to degradation of much of spores' rRNA (12).…”
mentioning
confidence: 99%
“…This issue was addressed in a landmark study in 2015 by Sinai et al (3). These authors showed, first, that protein synthesis occurs prior to the completion of germination in two ways: (i) by a novel biochemical approach (bio-orthogonal noncanonical amino acid tagging [BONCAT]) that specifically identifies newly synthesized proteins and (ii) by monitoring the timing, during germination, of the appearance of fluorescently tagged versions of some of the proteins discovered by BONCAT.…”
mentioning
confidence: 99%